Standardization of Word Order in Toponyms-Word Combinations - I. A. Dambuev (Tsentr nauchnykh i obrazovatelnykh proektov, 2019)
The article is devoted to the study of the standardization of the order of words in the attribute toponyms - word combinations with the type of concord connection. The relevance of the study is due to the need to understand the results of the standardization of toponyms in Russia in order to create linguistic foundations for its improvement. The novelty of the work lies in the fact that the study of the results of the standardization of toponyms is carried out for the first time on the basis of the variation of the word order in toponyms and word combinations. Using statistical analysis, it is shown that simple toponyms-word combinations are the nuclear type of toponyms-word combinations in Russian toponymy. Examples of variation of the direct and reverse order of words in toponyms-word combinations are presented. The most frequent post-positive definitions in toponyms-word combinations with inverse word order are revealed. Parallels are drawn between terminological word combination and toponyms-word combinations with inverse word order. Special attention is paid to the analysis of toponyms-word combinations normalized in recent years with varying word order. The author makes the assumption that the use of ordinal numbers in toponyms-word combinations in an inverted form is supported by the rules of writing toponyms on maps. The connection between the choice of codified variant and the features of the regional toponymic system is established. The necessity of continuing observations on the process of the standardization of toponyms to confirm the results obtained is emphasized.